Deposição e caracterizações óptica e morfológica de filmes finos de TIOX depositados por sputtering R.F. - Abreu, Caio Palumbo de (2013)
This work studied ultrathin films of titanium oxide were deposited on two substrates, such as pure Si (100) and glass corning 7059, by using r.f. magnetron sputtering with different oxygen flows and maintaining another parameters constant. For the purpose of this work, while keeping all parameters constant, varying only the oxygen flow (reactive gas), it was expected to identify the flow of transition between films of substoichiometric TiOx and TiO2 films, and analyze whether there forming nanostructured TiO2 films because the literature shows that variation of control parameters important characteristics of the nanoparticles as medium sized fraction of coverage of the substrate crystal structure and stoichiometry. The chemistries of the ultrathin films were analyzed through technique of Rutherford Backscattering Spectroscopy (RBS), the surface morphology by Atomic Force Microscopy (AFM), the crystallinity by X-Ray Diffraction (XRD) and the optical properties by UV-vis Spectroscopy. Were deposited ultrathin films with substoichiometric compositions for depositions with 0.10% O2 and 0.35% O2. For depositions between 0.67% O2 and 6.00% O2, films were obtained with concentrations of [O]/[Ti] of about 1.9, near the chemical composition of titanium dioxide (TiO2). Films with concentrations close to the TiO2 showed amorphous, but with characteristics of formation of anatase phase. The optical properties presented optical gap values between 3.33 eV and 3,78 eV and had no significant variation, as calculated by E03, E04 and ETauc methods. The roughness of the films decreased proportionally with increasing oxygen flow in the depositions.